Ultrasonographic manifestations and misdiagnosis analysis of ovarian leiomyoma - Zhang, Min; Hong, Yan; Wang, Li; Qin, Ling-Ling; Jing, Xiang-xiang (Frontiers in Medicine, 2023)
Objectives Ovarian leiomyomas (OLs) are rare and account for only 0.5 to 1% of benign ovarian tumors. This study investigated the ultrasonographic manifestations of OL and the potential reasons for misdiagnosis. Methods Between July 2018 and July 2023, 7 patients diagnosed with OL by surgical pathology and immunohistochemistry were enrolled in this retrospective analysis. Ultrasound (US) examinations were performed before surgery. Clinical characteristics, pathological findings, ultrasonographic manifestations, and treatment were reviewed. Results The mean age of the 7 patients was 39.0 ± 11.57 years, with a disease course of 0.1 to 24 months. All ovarian leiomyomas were unilateral. Four cases occurred in the right ovary, and three cases occurred in the left ovary. All lesions presented as hypoechogenic, well-circumscribed, round or oval in shape, and regular in morphology. No significant blood flow signal was detected peripheral to or inside the mass in 3 cases (42.8%), and a minimal flow signal was detected peripheral to or inside the mass in 4 cases (58.2%). A total of 7 ultrasonographic images of OL were misdiagnosed: 1 patient was misdiagnosed with subserosal uterine leiomyoma, and 6 patients were misdiagnosed with a tumor in the ovarian thecoma–fibroma group. Conclusion The imaging manifestation of OL lacks specificity; thus, preoperatively distinguishing OL from other ovarian tumors and subserosal uterine leiomyomas is difficult. Immunohistochemistry may be helpful for the definitive diagnosis of OL. The possibility of ovarian leiomyoma should be considered in patients with uterine leiomyomas coexisting with an adnexal ovarian solid mass.